DESIGN AND PROTOTYPE DEVELOPMENT OF AN IOT-BASED TEMPERATURE AND HUMIDITY MONITORING SYSTEM WITH REAL-TIME DATA AND AUTOMATED ALERTS - Wivanius, Nadhrah; Isranda Sihombing, Willy; Kamsyah, Domi (Politeknik Negeri Batam, 2025)
This study presents the design and implementation of an Internet of Things (IoT)-based system for real-time monitoring of room temperature and humidity. The system integrates a DHT11 sensor with an ESP32-C3-WROOM-2 microcontroller to measure environmental parameters within ranges of 0–50 °C and 20–90% relative humidity, achieving accuracies of ±2°C and ±5% RH, respectively. Measurement data are displayed on a 20×4 I2C LCD and transmitted wirelessly via Wi-Fi to Google Sheets for cloud-based storage and analysis. The system features an automatic notification mechanism that sends alerts through WhatsApp when environmental conditions exceed predefined thresholds. Calibration testing against the HTC-2 reference standard device demonstrated a total average measurement error of 1.594%, confirming compliance with the DHT11 sensors specified tolerance limits. Consistency tests conducted in both air-conditioned and non-air-conditioned environments revealed that the system effectively captures genuine environmental variations, with higher variability observed in mechanically controlled spaces due to HVAC operational cycles. The developed prototype successfully addresses limitations of conventional monitoring methods by eliminating manual intervention requirements, enabling continuous real-time surveillance, and facilitating rapid preventive actions. Results indicate that the system provides sufficient measurement accuracy and stability for practical applications in residential, commercial, and industrial environmental monitoring, while offering a cost-effective and accessible solution for IoT-based climate control systems.